Philosophical Basis of Social Responsibility Regulation of Limited Companies in Indonesia - fahmi, fahmi; Putra, Trianggara (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The problem of the philosophical basis of the regulation of limited liability company social responsibility in Indonesia. The occurrence of this shift raises a number of issues that are worthy and important to be studied related to the philosophical foundation of corporate social responsibility. This is important to explore because social responsibility has a different philosophical basis from the philosophical foundation of legal responsibility. The mention uses the term corporate social responsibility but has the meaning of legal obligations and responsibilities. It is necessary to study the basis for the shift in responsibility and the legal consequences of the shift. This research is a normative juridical law research using a positive law enforcement approach. Because philosophically the application of corporate social responsibility by the company describes that the company as a personification that the legal subject is not only a business entity that only seeks profit, but the company is also a social entity that interacts with its environment both in economic, social and environmental aspects. the company carries out its business activities.